2018
DOI: 10.3389/fnana.2018.00061
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotypes Associated to Engrailed 2 Gene Alterations in a Series of Neuropediatric Patients

Abstract: The engrailed homeobox protein (EN) plays an important role in the regionalization of the neural tube. EN distribution regulates the cerebellum and midbrain morphogenesis, as well as retinotectal synaptogenesis. In humans, the EN1 and EN2 genes code for the EN family of transcription factors. Genetic alterations in the expression of EN2 have been related to different neurologic conditions and more particularly to autism spectrum disorders (ASD). We aimed to study and compare the phenotypes of three series of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…Subsequently, it was found that EN signaling was also required for proper targeting of cerebellar mossy fiber afferents (Sillitoe et al, 2010). Building on the original EN association studies (Gharani et al, 2004), a recent report has confirmed the importance of EN signaling in the manifestations of ASD, while also finding that the clinical manifestation of the disease was not tightly associated with the particular polymorphism expressed in a given affected patient (Carratala-Marco et al, 2018). This may not be surprising given the complexity of somatotopy in cerebellar function (Apps and Hawkes, 2009) as well as the finding that multiple molecular mechanisms, not just EN, are required for cerebellar patterning in both the AP and ML axes (Sillitoe and Joyner, 2007;White and Sillitoe, 2013).…”
Section: Mouse Models Of Cerebellar Cognitive Disordersmentioning
confidence: 96%
“…Subsequently, it was found that EN signaling was also required for proper targeting of cerebellar mossy fiber afferents (Sillitoe et al, 2010). Building on the original EN association studies (Gharani et al, 2004), a recent report has confirmed the importance of EN signaling in the manifestations of ASD, while also finding that the clinical manifestation of the disease was not tightly associated with the particular polymorphism expressed in a given affected patient (Carratala-Marco et al, 2018). This may not be surprising given the complexity of somatotopy in cerebellar function (Apps and Hawkes, 2009) as well as the finding that multiple molecular mechanisms, not just EN, are required for cerebellar patterning in both the AP and ML axes (Sillitoe and Joyner, 2007;White and Sillitoe, 2013).…”
Section: Mouse Models Of Cerebellar Cognitive Disordersmentioning
confidence: 96%
“…A recent study [73] reported that En1 shows a transcriptional dependency in triple negative breast cancer associated with brain metastasis. Carratala-Marco et al [74] found that EN plays an important role in the regionalization of the neural tube and EN’s distribution regulates cerebellum and midbrain morphogenesis, as well as retinotectal synaptogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Two intronic EN2 polymorphisms have been genetically associated with ASD and have been shown in independent cohorts and populations to be overtransmitted to autistic offspring from heterozygous parents (reviewed in Brune et al, 2008;Choi et al, 2011;Kuan et al, 2015;Sen et al, 2010;Wang et al, 2008). Additionally, rare mutations in EN2 have been reported in ASD patients (Carratala-Marco et al, 2018;Hnoonual et al, 2016), and dysregulation of EN2 expression has been observed in two independent studies of postmortem cerebellar tissue in ASD (Choi et al, 2014;James et al, 2013). Thus, autism-related behaviors in the En2-KO such as learning deficits and depressive phenotypes can be influenced by abnormal neurogenesis and reduced numbers of neurons in the hippocampus (Genestine et al, 2015) and directly regulated by hippocampal expression of En2.…”
Section: En2 and Neurodevelopmental Disordersmentioning
confidence: 99%